Topics in Osteoporosis - Valdes Flores, Margarita (IntechOpen, 2013)
Osteoporosis affects the osteo-articular system. However, there are hormonal, kidney related, gastrointestinal and neuromuscular factors among other, that can be involved in the etiopathogenesis of the disease. In the other hand, for osteoporosis prevention there are many lifestyle conditions that are very important, as dietary habits, physical activity, drugs and caffeine intake, smoking, associated diseases, etc. Based on the above, treatment and prevention of osteoporosis have to be addressed in a multidisciplinary and integral approach. The knowledge about bone metabolism and the related disorders represents an extensive field that is currently increasing through many investigations conducted in the world. The purpose of this book is to show several reviews and original investigations related with osteoporosis.